PENGEMBANGAN PERANGKAT PEMBELAJARAN DENGAN STRATEGI BELAJAR TUNTAS UNTUK MENINGKATKAN HASIL BELAJAR FISIKA MATERI HUKUM NEWTON DAN PENERAPANNYA DI KELAS X - Stefany Margareta Martono (LPPM Politeknik Saint Paul Sorong, 2019)
Development Device with Mastery Learning Strategy to Improve Learning Outcomes Physics and Implementation of the Newton's Law in class X. The development is one way to create new innovations in learning activities in the classroom. The purpose of this research is 1) To get the proper and purposeful learning, combined with mastery learning strategies to improve learning outcomes in the material physics of Newton's laws in class X. 2) For the effectiveness of the learning device combined with mastery learning strategies to improve student learning outcomes on Newton's laws of matter in class X. this study uses a